2023
DOI: 10.3389/fmed.2022.1059747
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of bioelectrical impedance phase angle for critically ill patients: A systemic review and meta-analysis

Abstract: ObjectiveBioelectrical impedance-derived phase angle (PA) has exhibited good prognostic values in several non-critical illnesses. However, its predictive value for critically ill patients remains unclear. Thus, we aimed to perform a systematic review and meta-analysis to investigate the relationship between PA and survival in such a patient population.Materials and methodsWe searched for relevant studies in PubMed, Embase, and the Cochrane database up to Jan 20, 2022. Meta-analyses were performed to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
2
4
0
Order By: Relevance
“…In the ICU, a consistent association of the phase angle with the outcomes, independent of the current severity scoring systems, was reported in the literature. In our opinion, this supports its use as a candidate variable 7 for future severity scoring systems. The current study suggests the relevance of an approach combining the phase angle and hemodynamic and myocardial damage parameters to predict outcomes in postoperative care after cardiac surgery.…”
Section: To the Editorsupporting
confidence: 67%
“…In the ICU, a consistent association of the phase angle with the outcomes, independent of the current severity scoring systems, was reported in the literature. In our opinion, this supports its use as a candidate variable 7 for future severity scoring systems. The current study suggests the relevance of an approach combining the phase angle and hemodynamic and myocardial damage parameters to predict outcomes in postoperative care after cardiac surgery.…”
Section: To the Editorsupporting
confidence: 67%
“…Most changes in body composition and nutritional status in participants undergoing the nutritional intervention were too small to be detected by bioelectrical impedance [ 29 ]. To date, this method has been used mainly for evaluating the effectiveness of training programs in athletes and monitoring the nutritional status of critically ill patients [ 30 , 31 ]. Results reported in these studies suggest that bioelectrical impedance could also be helpful in dietary intervention contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced PA can be diagnosed when PA is below 5.0° in males and 4.6° in females (Girma T et al,2017). A decrease in PA indicates poor prognosis, increased complications, and shortened survival (Zheng WH et al,2023;Scicchitano P et al,2022). This study's results revealed a strong negative correlation between PA and ECW/TBW (correlation coe cient rs=-0.896, P<0.001).…”
Section: Explanation Of Ecw/tbw Univariate Analysis Resultsmentioning
confidence: 54%